Levamisole-contaminated cocaine: a hairy affair. (26th August 2015) - van der Veer, Tjeerd; Pennings, Ed; Tervaert, J W Cohen; Korswagen, Lindy-Anne
Abstract : Levamisole-contaminated cocaine can induce severe systemic vasculitis. The diagnosis can be challenging, especially when substance abuse is uncertain. We present the case of a 42-year-old woman suffering from vasculitis due to levamisole-contaminated cocaine, who persistently denied substance abuse. Symptoms included ulcerating skin lesions, arthralgia and myalgia, and the occurrence of an ileal intussusception. The definitive diagnosis was made using hair testing for toxins. She recovered through cocaine abstinence, but re-exposure resulted in a severe relapse with glomerulonephritis. Importantly, at time of the relapse, the patient became positive for both myeloperoxidase-antineutrophil cytoplasmic antibody (ANCA) and proteinase 3-ANCA. Cocaine–levamisole-induced vasculitis poses a great clinical challenge. The proper diagnostic strategy and therapy is still controversial. We highlight our diagnostic and therapeutic considerations, including hair testing for definitive proof of exposure.